The application of GIS-AHP technique in analysing the level of the environmental condition of forested areas - Asmawi, M. Zainora; Ngaimin, Najihah; Mahamod, Noor Zalina; Hj. Mohd. Noor, Norzailawati; Omar, Hamdan (2017)
Forests are major resources that offer a strong artistic, cultural, biological and economical source for the social community in every nation. Degradation of the environmental condition has become a key concern, and the primary cause of this trouble is linked primarily to human disturbance towards natural resources. Therefore, this research was embarked to analyse the level of the environmental status of forested areas in Forest Research Institute Malaysia (FRIM), Selangor, Malaysia-based on chosen measures. This research depends on a series of GIS database covering five criteria, namely slope, altitude, crown perimeter, tree height and carbon stock, which were then analysed using Analytic Hierarchy Process (AHP). A scoring system was developed from eigenvalue of priority ratings and bringing out a composite map, showing the level of the environmental condition of the forest, ranging from the healthiest, moderately healthy and less healthy condition. The results indicate that 45.5% of the forested areas in FRIM lie under the category of healthiest condition (220.8 hectares) with the carbon stock as the key contributor. This research concludes that the relevant criteria for ecosystem health are beneficial in monitoring the forest condition that contributes to the environmental quality with particular reference to the consideration of forest as an impactful carbon sink element of any geographical setting.